Projectile and Fragment Penetration in Snow and Frozen Soil - Aitken, George W.; Swinzow, George K.; Farrell, Dennis R. (1976)
The work was accomplished as part of an investigation of terminal ballistics in snow, ice and frozen soil. The objective are to develop design criteria for effective utilization of indigenous cold regions materials in field fortifications, to develop methods for estimating the terminal effectiveness of remotely emplaced munitions and sensor systems, and to evaluate foreign expertise in these areas. To accomplish these objectives, a number of laboratory and field investigations were conducted to quantify the effectiveness of various projectiles fired into snow, ice and frozen soil targets. Penetration data from these tests were analyzed using a theory developed for use with unfrozen soil targets and were found to be in reasonable agreement with predicted penetrations in both snow and frozen soil.